(untitled) (Journal of Asian Development Studies, 2021)
Small and Medium-sized Enterprises (SMEs) have scarce resources, lack of knowledge and skills yet many examples exist of SMEs that are engaged in export activities. A unique category of SMEs that have not only overcome their resource constraints to internationalize but also have engage in exporting activities from very start of their businesses are called “born international”. This study attempts to investigate the existence of the entrepreneurial orientation (EO) construct in the context of born-international SMEs who are operating in the surgical instruments industry of Sialkot. Purposive sampling technique has been applied to select respondents and questionnaire is used to collect data. The findings suggest that EO exists in born international firms with innovation and risk-taking as dominant dimensions of EO that prevails in such firms.